Efficacy of Prompt Initiation of Antiretroviral Therapy in the Treatment of Hemophagocytic Lymphohistiocytosis Triggered by Uncontrolled Human Immunodeficiency Virus. (10th August 2017) - Fitzgerald, Bryan P.; Wojciechowski, Amy L.; Bajwa, Rajinder P. S.
Abstract : Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening, rapidly progressive hematologic disorder involving uncontrolled immune system activation. HLH has been associated with viral infections, including human immunodeficiency virus (HIV) infections. We report a case of a critically ill 30-year-old female who was hospitalized with HIV-associated HLH, with a CD4 count of 4 cells/mL and HIV viral load of 1, 842, 730 copies/mL. After ruling out other potential infectious causes of HLH, antiretroviral therapy (ART) was initiated with darunavir, ritonavir, tenofovir, and emtricitabine. Within one week of initiation of ART, the patient began to improve clinically and hematologically and was stable enough for discharge from the hospital three weeks after starting therapy. This case suggests that treatment with ART in patients with HIV-associated HLH should be considered even in critically ill patients with low CD4 counts.